Predictors of parental pedestrian safe road behaviour in rural areas in Malaysia - Tamil Selvan, Hari Krishnan; Subramaniam, Kulanthayan; Juni, Muhamad Hanafiah; Md Said, Salmiah (Diva Enterprises, 2014)
Objective The study was done to assess the predictors of pedestrian safe road behaviour of parents with their children in the rural areas of Rembau, Negeri Sembilan, Malaysia. Method A cross sectional survey was conducted among parents in the rural areas of Rembau, Negeri Sembilan from September to December 2010. The simple random sampling method was used for selection of the respondents for the study and data were collected through face-to-face interviews using a structured questionnaire. Results A total of 202 respondents participated in the research with a 78%response rate. There is a significant mean difference between parental safe road behaviour and education status (p=0.012), household income (p=0.000), occupational class (p=0.012) and the presence of playgrounds (p=0.014). However, in multiple linear regression analyses only household income emerged as a significant factor (p=0.004). Conclusion Parents with higher income showed higher safe road behaviour while being a pedestrian walking their children on the road.